Ephemera and the British Empire - colour illustrations - Tomkins, D; Jackson, A (University of Oxford, 2015)
8 colour illustrations for Chapter 6 ‘Ephemera and the British Empire’ by Ashley Jackson & David Tomkins, to be published in the collected volume ‘Exhibiting the Empire: cultures of display and the British Empire’, edited by John M. MacKenzie and John McAleer, published in 2015 by Manchester University Press.